Predicting factors of zone 4 attack in volleyball - Costa, G. C.; Castro, H. O.; Evangelista, B. F.; Malheiros, L. M.; Greco, P. J.; Ugrinowitsch, H. (Perceptual and Motor Skills, 2017)
This study examined 142 volleyball games of the Men`s Super League 2014/2015 seasons in Brazil from which we analyzed 24-26 games of each participating team, identifying 5,267 Zone 4 attacks for further analysis. Within these Zone 4 attacks, we analyzed the association between the effect of the attack carried out and the separate effects of serve reception, tempo and type of attack. We found that the reception, tempo of attack, second tempo of attack, and power of diagonal attack were predictors of the attack effect in Zone 4. Moreover, placed attacks showed a tendency to not yield a score. In conclusion, winning points in high-level men's volleyball requires excellent receptions, a fast attack tempo and powerfully executed of attacks.